(untitled) (Circe de clásicos y modernos, 2018)
Although it is not possible to speak about the absence of a political dimension in the Poetics, it is undeniable the fact that exists an evident asymmetry between this work and the two last books of the Politics with regard to the consideration of the political and pedagogical aspects that the mimetic arts necessary involve. By means of this work, I attempt to prove that this dissimilarity is inherent to the way in which Aristotle conceive the mimetic arts and through it, reveals the originality of his thinking in this respect.